Ionic liquid modified bacterial cellulose-based packaging material as well as preparation method and application thereof
By grafting 1-vinyl-3-aminopropylimidazole gallic acid ionic liquid on bacterial cellulose, forming an ionic liquid-modified bacterial cellulose-based packaging material, solving the problem of poor water vapor discharge of existing packaging materials, achieving high moisture permeability, antibacterial and antioxidant effects, and extending the shelf life of fruits and vegetables.
Patent Information
- Application Number
- CN202510083639.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing bacterial cellulose-based packaging materials have low water vapor transmission during the preservation process of fruits and vegetables, resulting in the inability to effectively discharge the water vapor in the packaging, resulting in the problem of preservation failure.
By grafting 1-vinyl-3-aminopropylimidazole gallic acid ionic liquid on bacterial cellulose, an ionic liquid-modified bacterial cellulose-based packaging material is formed to enhance its antibacterial, antioxidant and moisture permeability.
It significantly enhances the moisture permeability, antibacteriality and antioxidant properties of packaging materials, effectively extends the shelf life of fruits and vegetables, and maintains the quality during storage.
Smart Images

Figure CN119875015A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of bacterial cellulose-based packaging materials, and in particular relates to an ionic liquid-modified bacterial cellulose-based packaging material and a preparation method and application thereof. Background Art
[0002] In recent years, the production and consumption of fruits and vegetables have increased significantly worldwide. However, their post-harvest quality is still subject to many factors such as physiological state, respiration, transpiration and storage conditions. In particular, the water vapor produced by fruits and vegetables during respiration and transpiration after harvest will condense on the inner surface of the packaging film, affecting the visual beauty of the product and consumer experience. In addition, when condensed water droplets roll off the film surface, they may also provide an ideal growth environment for microorganisms, further threatening the quality and safety of the product. Take raspberries as an example. It is a fruit with a high respiration rate. After harvest, it continues to respire vigorously, consumes nutrients and produces a large amount of water vapor. If the water is not effectively discharged, the raspberries will be in a high humidity environment, which will accelerate the reproduction of fungi and other microorganisms, leading to corruption and deterioration. These problems highlight the importance of developing packaging films with high moisture permeability, antibacterial properties and antioxidant properties for the preservation of fruits and vegetables.
[0003] The wide availability of cellulosic waste provides great potential for the development of green and sustainable materials. Among them, bacterial cellulose (BC), a natural polymer compound produced by Gluconacetobacter xylinum, has attracted much attention due to its excellent properties. The chemical structure of BC is the same as that of plant cellulose, both of which are composed of D-glucose repeating units cross-linked by β-1,4-glycosidic bonds. However, compared with plant cellulose, BC exhibits higher elastic modulus, tensile strength, crystallinity, water holding capacity and biocompatibility. With these excellent properties, BC has been widely used in wound dressings, artificial skin matrices, paper and textiles, and edible packaging films.
[0004] Despite this, the application of BC in the field of food packaging is still limited by its deficiencies in antibacterial properties, antioxidant properties, moisture permeability and stress resistance. To this end, researchers have tried to give BC different functionalities through different physical or chemical modification methods. Ionic liquids are a type of molten salt composed of organic cations and organic or inorganic anions. As an advanced functional material, their excellent structural adjustability makes them widely used in antibacterial, catalytic, synthetic chemistry and electrochemistry. In particular, the inherent antibacterial properties and structural adjustability of quaternary ammonium salt ionic liquids can become a new type of modification agent for the construction of highly efficient antibacterial materials. For example, the patent application document with publication number CN118459668 A discloses a polyionic liquid modified bacterial cellulose-based packaging film material, a preparation method and application thereof, and a packaging material with antibacterial, antioxidant and hydrophobic properties is prepared by grafting 1-vinyl-3-aminopropyl imidazole tryptophan ionic liquid functional modification reagent on bacterial cellulose (BC). However, for fruits with high respiration intensity, there is still a problem of easy saturation of water vapor in the packaging. When the storage environment temperature fluctuates, the water vapor will condense into water droplets, thereby leading to the growth of harmful microorganisms and accelerating the risk of fruit decay. Summary of the invention
[0005] The purpose of the present invention is to provide an ionic liquid modified bacterial cellulose-based packaging material and a preparation method and application thereof, so as to solve the problem in the prior art that the water vapor permeability of the PE-based film is too low, and the excess water vapor generated after long-term packaging cannot be discharged, resulting in the failure of preservation, thereby effectively extending the shelf life and maintaining the quality during storage.
[0006] The present invention is achieved through the following technical solutions:
[0007] The invention discloses an ionic liquid modified bacterial cellulose-based packaging material, wherein the packaging material is obtained by modifying and grafting 1-vinyl-3-aminopropyl imidazole gallic acid ionic liquid on bacterial cellulose.
[0008] Furthermore, the packaging material is obtained by reacting bacterial cellulose with N,N'-carbonyldiimidazole and bis(carboxymethyl)trithiocarbonate to obtain modified grafted BC-CTA, and then grafting 1-vinyl-3-aminopropylimidazole gallic acid ionic liquid on BC-CTA.
[0009] A method for preparing an ionic liquid-modified bacterial cellulose-based packaging material comprises the following steps:
[0010] A certain amount of bacterial cellulose is added to dimethyl sulfoxide for full impregnation, and then reacted with N,N'-carbonyldiimidazole (1.4 times the amount of bacterial cellulose) at 30-40°C in the dark, and then the reaction product is reacted with bis(carboxymethyl)trithiocarbonate (1.4 times the amount of bacterial cellulose) at 30-40°C in the dark to obtain BC-CTA;
[0011] The BC-CTA and 1-vinyl-3-aminopropyl imidazole gallic acid ionic liquid are immersed in dimethyl sulfoxide, and under the action of initiator AIBN, they are sealed and heated to 70-75° C. in an inert gas atmosphere to react, thereby obtaining an ionic liquid-modified bacterial cellulose-based packaging material.
[0012] Furthermore, the preparation of the 1-vinyl-3-aminopropyl imidazole gallic acid ionic liquid is specifically as follows:
[0013] First, gallic acid was added to a methanol solution to obtain a 0.2 mmol / mL gallic acid solution, and then an equal amount of 1-vinyl-3-aminopropyl imidazole hydroxide aqueous solution was added to the gallic acid solution, reacted at 0°C for 1 hour, the solvent was evaporated by a rotary evaporator under vacuum, and the product was dried under reduced pressure at 25°C for 24 hours to obtain 1-vinyl-3-aminopropyl imidazole gallic acid ionic liquid.
[0014] Further, the preparation of the 1-vinyl-3-aminopropyl imidazole hydroxide aqueous solution is specifically as follows:
[0015] Dissolve 3-bromopropylamine hydrobromide in water, add an equimolar amount of sodium hydroxide, and react to generate 3-bromopropylamine;
[0016]
[0017] 1-vinyl imidazole and the 3-bromopropylamine in a molar ratio of 1:1 are refluxed at 60-65° C. under an inert gas atmosphere to obtain 1-vinyl-3-aminopropyl imidazole bromide;
[0018]
[0019] The 1-vinyl-3-aminopropyl imidazole bromide is dissolved in water and passed through a 201×7 type anion exchange resin to obtain an aqueous solution of 1-vinyl-3-aminopropyl imidazole hydroxide.
[0020] Furthermore, the usage of the 201×7 type anion exchange resin is 1.3 g of resin per mole of ionic liquid.
[0021] Application of an ionic liquid modified bacterial cellulose-based packaging material in an antibacterial film.
[0022] Application of bacterial cellulose-based packaging material modified by ionic liquid in food cling film.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention adopts an innovative antibacterial and antioxidant ionic liquid monomer 1-vinyl-3-aminopropyl imidazole gallic acid ([Vaim][GA]), which is modified by grafting polymerization technology, and [vaim][GA] is successfully grafted onto bacterial cellulose. Firstly, due to the presence of the ionic liquid, the quaternary ammonium salt structure in the molecule and the presence of gallic acid provide high-efficiency and broad-spectrum antibacterial properties; secondly, gallic acid can effectively remove a variety of free radicals and provide antioxidant properties; thirdly, hydrophilic gallic acid gives the BC film high moisture permeability to prevent water condensation from causing bacterial growth; the present invention significantly enhances the antibacterial, antioxidant and moisture permeability properties of the BC film, and through the use of bacterial cellulose, reduces the dependence on petroleum-based materials, provides an environmentally friendly and biodegradable solution, effectively prolongs the shelf life and maintains the quality during storage.
[0025] In summary, the packaging material prepared by the present invention has high moisture permeability, continuous antibacterial and antioxidant properties, and promotes the breakthrough development of preservation technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Graph showing the water contact angles of BC and samples with different grafting degrees of the present invention.
[0027] Figure 2 This is a test chart of water vapor transmission rate of BC and samples with different grafting degrees of the present invention.
[0028] Figure 3 It is a test diagram of the moisture permeability of PE, BC and samples with different grafting degrees of the present invention.
[0029] Figure 4(a) is a colony distribution diagram of BC and samples of different grafting degrees of the present invention against Gram-negative bacteria and Gram-positive bacteria, and Figure 4(b) is a diagram of the inhibition rate of BC and samples of different grafting degrees of the present invention against Gram-negative bacteria and Gram-positive bacteria.
[0030] Figure 5 This is a graph showing the scavenging rates of BC and samples of the present invention with different grafting degrees on DPPH free radicals, ABTS free radicals, and ·OH free radicals.
[0031] Figure 6 The cell viability diagram after exposure to BC and samples with different grafting degrees of the present invention.
[0032] Figure 7 The figure shows the antibacterial test results of raspberries in different packaging. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] A method for preparing an ionic liquid-modified bacterial cellulose-based packaging material, comprising:
[0036] S1. Synthesis of 3-bromopropylamine salt
[0037]
[0038] Dissolve 3-bromopropylamine hydrobromide in water, add an equimolar amount of sodium hydroxide, and react to generate 3-bromopropylamine.
[0039] S2. Synthesis of 1-vinyl-3-aminopropyl imidazole bromide
[0040]
[0041] 1-Vinyl imidazole and 3-bromopropylamine in a molar ratio of 1:1 were mixed in a round-bottom flask and refluxed at 60°C for 20 hours under a nitrogen atmosphere to form a yellow viscous liquid. After the reaction was completed, it was cooled to room temperature, washed thoroughly with ethyl acetate, and dried under reduced pressure at room temperature for 48 hours to obtain 1-vinyl-3-aminopropyl imidazole bromide.
[0042] S3. Preparation of 1-vinyl-3-aminopropyl imidazole hydroxide aqueous solution
[0043] The synthesized 1-vinyl-3-aminopropyl imidazole bromide is dissolved in water and passed through a 201×7 type anion exchange resin, wherein the amount of the 201×7 type anion exchange resin used is 1.3 g of resin per mole of ionic liquid to obtain a 1-vinyl-3-aminopropyl imidazole hydroxide aqueous solution.
[0044] S4. Preparation of 1-vinyl-3-aminopropyl imidazole gallic acid ionic liquid
[0045] First, 1.701 g of gallic acid was added to 50 mL of methanol solution to obtain a gallic acid solution, and then 50 mL of 1-vinyl-3-aminopropyl imidazole hydroxide aqueous solution was added to the gallic acid solution, and the neutralization reaction was carried out at 0° C. for 1 hour. Finally, the solvent was evaporated by a rotary evaporator under vacuum, and the product was dried under reduced pressure (5 mbar) at 25° C. for 24 hours to obtain 1-vinyl-3-aminopropyl imidazole gallic acid ionic liquid.
[0046] S5. Preparation of BC-CTA
[0047] 500 mg of bacterial cellulose was placed in DMSO, reacted with 700 mg of N,N'-carbonyldiimidazole at 30-40° C. in the dark, and then reacted with 700 mg of bis(carboxymethyl)trithiocarbonate at 30-40° C. in the dark to obtain BC-CTA.
[0048] S6. Bacterial cellulose-based packaging materials modified by ionic liquids
[0049] The 500 mg BC-CTA and 500 mg 1-vinyl-3-aminopropyl imidazole gallic acid ionic liquid were added to DMSO, and sealed and heated to 70-75° C. in an inert gas atmosphere under the action of initiator AIBN for reaction for 18 hours. The sample was taken out and washed with DMSO until the washing liquid was colorless, then washed with deionized water, and finally placed in a vacuum drying oven at 80° C. for 4 hours to obtain an ionic liquid-modified bacterial cellulose-based packaging material, named BC-CTA@PIL1.
[0050] Example 2
[0051] A method for preparing an ionic liquid modified bacterial cellulose-based packaging material is basically the same as that of Example 1, except that in step S6, the amount of 1-vinyl-3-aminopropyl imidazole gallic acid ionic liquid used is 1000 mg, and is named BC-CTA@PIL2.
[0052] Example 3
[0053] A method for preparing an ionic liquid-modified bacterial cellulose-based packaging material is basically the same as that of Example 1, except that in step S6, the amount of 1-vinyl-3-aminopropyl imidazole gallic acid ionic liquid used is 1500 mg, and is named BC-CTA@PIL3.
[0054] Contact angle and water vapor transmission rate test
[0055] The water contact angle was examined using an optical contact angle measuring device (OCR20, Germany). The modified ASTM E96-95 method (ASTM, 1995) was used to measure the water vapor permeability of the samples. 3.0 g of pre-dried anhydrous calcium chloride was placed in a weighing bottle, and then the PE film, original and modified BC film were attached to the top of the bottle (the effective area of the film was 0.001256 square meters) and fixed with an elastic band. The weighing bottle covered with the film sample was then placed in a desiccator with a saturated sodium chloride solution (75% RH) at the bottom and maintained at 25°C. The change in the weight of the bottle was described as a function of time at intervals of 2 hours within 12 hours, accurate to 0.0001 grams. The slope (K) (g / s) of each line was calculated by linear regression, and the water vapor transmission rate (WVTR) per unit area (g / h·m 2 ):
[0056]
[0057] Where K is the humidification weight per unit time (g / s), A is the exposed membrane area (0.001256m 2 ). The WVTR of each film sample was measured three times.
[0058] like Figure 1 As shown in the figure, the WCA of pure BC membrane is 32.4°, indicating that it is hydrophilic. The WCA of BC-CTA@PIL1 membrane, BC-CTA@PIL2 membrane, and BC-CTA@PIL3 membrane are 26.8°, 21.3°, and 15.7°, respectively. The results show that the hydrophilicity of bacterial cellulose membrane increases with the increase of grafting degree. This is because the added PIL chain contains multiple hydrophilic groups, especially the multiple phenolic hydroxyl groups (-OH) of the gallic acid part. After grafting, these hydroxyl groups are exposed on the surface of the cellulose membrane, forming more hydrogen bonds with water molecules, enhancing the hydrophilicity of the surface, and resulting in a decrease in the contact angle.
[0059] WVTR is crucial in the process of food packaging materials. Good water vapor barrier properties can effectively prevent water vapor in the environment from entering the food, thereby effectively extending the shelf life of the food. Figure 2 As shown in Figure 2, the WVT of BC-CTA@PIL film is 2006.5 g / m 2 ·day, with the increase of ionic liquid grafting degree, the WVT value increases, indicating an increase in water vapor transmission rate, which is attributed to the introduced hydrophilic gallic acid, which promotes water permeation, and the fine micropores on the blend matrix and membrane surface, which provide a pathway for water permeation.
[0060] Moisture permeability test
[0061] Add 10 mL of deionized water into a 500 mL beaker, fix the temperature and humidity detection probe under the mouth of the beaker, cover the mouth of the beaker with PE film, BC film, BC-CTA@PIL1 composite film, BC-CTA@PIL2 composite film, and BC-CTA@PIL3 composite film respectively, move the beaker to a 35 degrees Celsius water bath to heat it, and record the humidity values of the air above the beaker at 0 min, 5 min, 10 min, 20 min, and 30 min.
[0062] The results are as follows Figure 3 As shown, under the conditions of a 35°C water bath and 10 mL of water, the moisture permeability of the prepared composite membranes was compared by exploring the changes in the humidity of the air above the beaker. The humidity of the air above all beakers covered with sample membranes increased with time. With the continuous evaporation of water, the humidity in the air environment inside the PE film beaker reached 88.7% at 5 minutes, 99% at 10 minutes and remained there. In comparison, the humidity in the air environment inside the beaker of the pure BC membrane with hydrophilic groups reached 74% humidity at 5 minutes and stabilized at around 90% humidity after 20 minutes. In addition, the BC composite membrane grafted with hydrophilic groups has better moisture permeability. Specifically, with the increase in the degree of grafting, the stable humidity in the air environment inside the beaker continues to decrease within 30 minutes. This is because of the interaction between multiple hydrophilic groups from the PIL chain and water molecules on the film surface. Previous results have shown that the modification of ionic liquids enhances the hydrophilicity and water vapor permeability of the film surface. This property can prevent the formation of moisture inside the packaging due to transpiration during the transportation of fruits and vegetables, thereby avoiding a favorable environment for bacterial growth and preventing food spoilage. The results show that BC-CTA@PIL film can effectively solve the dehumidification problem inside the packaging of fresh fruits and vegetables.
[0063] Antibacterial performance test
[0064] To evaluate the antibacterial activity, representative Gram-negative bacteria (Escherichia coli E. coli) and Gram-positive bacteria (Staphylococcus aureus S. aureus) were selected as experimental strains. The strain was inoculated into a liquid culture medium and incubated with shaking for 12 hours. The cultured bacterial solution was diluted to an appropriate concentration and placed. Weigh 0.2g of bacterial cellulose membrane (BC, BC-CTA@PIL1, BC-CTA@PIL2, BC-CTA@PIL3), dissolve in dimethyl sulfoxide, and prepare a sample solution. 100μL of the sample solution was mixed with 900μL of the bacterial solution and incubated with shaking for 4h. The control group was replaced with the same amount of dimethyl sulfoxide solution, and then 100μL of the culture solution was applied to the solid culture medium. After incubation for a period of time, the number of surface colonies was counted. No UV light was used throughout the experiment.
[0065] The antibacterial rate was calculated using equation (2):
[0066]
[0067] Where:
[0068] CFU con ——The number of colonies on the culture medium of the control group (pieces);
[0069] CFU sam ——The number of colonies on the culture medium of the bacterial cellulose membrane experimental group (pieces).
[0070] The results are shown in Figure 4. The antibacterial results of the BC membrane modified with [vaim][GA] show that BC-CTA@PIL with different grafting degrees have different bactericidal effects against Escherichia coli and Staphylococcus aureus. Figure 4(a) shows that the pure BC group and the control group showed comparable colony counts, suggesting that the unmodified BC membrane lacks antimicrobial activity. In contrast, the BC-CTA@PIL series showed a discernible reduction in microbial counts. As shown in Figure 4(b), BC-CTA@PIL 1 showed a high antibacterial rate of 81.1% and 84.7% against the two tested strains, respectively. It is worth noting that with the increase in grafting density, BC-CTA@PIL 2 showed an antibacterial rate of more than 90%, while BC-CTA@PIL 3 showed an antibacterial rate of more than 95%, indicating a significant enhancement of the antimicrobial performance.
[0071] In summary, BC-CTA@PIL possesses excellent broad-spectrum antimicrobial properties due to the synergistic antimicrobial mechanism of [vaim][GA] and the fine-tuned grafting degree, and these findings suggest its potential to greatly enhance safety indicators in food packaging applications.
[0072] Scavenging activity assay
[0073] Scavenging activity evaluation method: DPPH determination: All samples were prepared into a solution with a concentration of 10.0 mg / mL for use. Different volumes (0.03, 0.06, 0.12, 0.24 and 0.48 mL) of sample solution were mixed with deionized water (0.97, 0.94, 0.88, 0.76 and 0.52 mL) to a total volume of 1 mL. The mixture was added to 2.0 mL of DPPH-ethanol solution (180 μmol / L) to a volume of 3.0 mL, and the final concentrations were 0.1, 0.2, 0.4, 0.8 and 1.6 mg / mL. Ethanol (2.0 mL) was used instead of 2.0 mL of DPPH-ethanol solution as a control, and 2.0 mL of deionized water and 2.0 mL of DPPH-ethanol solution were added to prepare a blank solution. The positive control was vitamin C (VC). The mixture was then incubated in the dark at room temperature for 20 minutes, the absorbance of DPPH free radicals was measured at 517 nm, and the DPPH free radical scavenging effect was calculated using formula (3):
[0074]
[0075] Among them, A sample 517nm is the absorbance of the sample, A control 517nm is the absorbance of the control, A blank 517nm is the absorbance of the blank.
[0076] ABTS assay: For the ABTS assay, an ABTS reagent containing 7 mM ABTS and 2.45 mM potassium persulfate was prepared and then incubated in the dark at room temperature for 16 hours. The freshly prepared reagent was then diluted with 80% ethanol to obtain the absorbance at 734 nm. In addition, 0.2 mL of sample solution of different concentrations (0-5 mg / mL) was mixed with 4 mL of diluted ABTS, and after incubation at room temperature for 6 minutes, Vc was used as a positive control, and the absorbance of the resulting mixture at 734 nm was measured. The free radical scavenging activity was calculated using formula (4):
[0077] RSA(%)=A0-(A1-A2) / A0×100 (4)
[0078] Wherein, A0, A1, and A2 represent the absorbance of the ABTS solution without sample, the absorbance of the test sample mixed with the ABTS solution, and the absorbance of the sample without ABTS solution, respectively.
[0079] Hydroxyl radical determination: Based on Fenton reaction (Fe 2+ +H2O2→Fe 3+ +OH-+·OH) was used to study the scavenging activity of the original and modified BC membranes towards hydroxyl radicals. To generate highly active hydroxyl radicals (·OH), the modified BC membranes were immersed in a mixed solution containing 6 mM ferrous sulfate (0.3 mL), 6 mM H2O2 (0.3 mL), 6 mM salicylic acid (0.3 mL) and pure water (0.3 mL). The mixture was then shaken vigorously and incubated at 37 °C for 60 min. The absorbance at 510 nm was measured and the hydroxyl radical scavenging activity was calculated using equation (5):
[0080]
[0081] Where D0 is the absorbance of the sample blank (no membrane added to the mixture), D1 is the absorbance of the membrane sample being tested, and D2 is the absorbance of the reagent blank (pure water instead of salicylic acid).
[0082] The results are as follows Figure 5As shown in the figure, BC exhibited a modest scavenging effect on DPPH radicals, ABTS radicals, and ·OH radicals at a concentration of 5 mg / mL, indicating limited antioxidant potential. However, with the increase of [vaim][GA] monomers grafted onto the BC matrix, the BC-CTA@PIL film exhibited significantly enhanced scavenging activity, and concentration-dependent scavenging activities for DPPH radicals, ABTS radicals, and ·OH radicals were observed. BC-CTA@PIL films had good scavenging abilities for DPPH radicals, ABTS radicals, and ·OH radicals. Notably, the scavenging rate of ABTS radicals reached 100% at a concentration of 5 mg / mL for BC-CTA@PIL 3 sample, which was attributed to the good antioxidant properties of imidazolium and GA by providing hydrogen atoms, acting as acceptors for free radicals, or interrupting the chain oxidation reaction by chelating metals. Therefore, the enhanced antioxidant properties of BC-CTA@PIL films are beneficial for their long-term application in food storage.
[0083] Safety evaluation experiment
[0084] Safety evaluation method: Cell counting kit-8 (CCK-8, Shanghai Beyotime Biotechnology Co. LTD) was used to perform cytotoxicity test on rat lung fibroblasts (L929, ATCC CCL-1, provided by Shanghai Cell Bank of Chinese Academy of Sciences). All samples were sterilized by ultraviolet irradiation for 0.5 h, and the extract of the composite membrane was obtained by soaking the sample in serum-free cell culture medium for 24 h, and the concentration was selected as 0.1 mg / mL. Cell viability and growth were evaluated 24 h after inoculation, and the triple average was used to reduce errors.
[0085] To ensure the biosafety of BC-CTA@PIL films for food packaging applications, the cytotoxicity of these films was carefully evaluated. The cytotoxic effects of BC CTA@PIL films were assessed using a quantitative CCK-8 assay, in which the viability of rat lung fibroblasts (L929) was used as a biological model. Figure 6As shown, the survival rate of L929 cells in the BC-treated group was consistent with that of the untreated control group, indicating the outstanding biocompatibility of natural BC materials and their promoting role in cell proliferation, and the slight decrease in cell viability associated with the BC-CTA@PIL membrane with the increase in the degree of PIL grafting. It is worth noting that the cells associated with the BC-CTA@PIL1 and BC-CTA@PIL2 membranes maintained more than 90% viability throughout the culture period, and even the BC-CTA@PIL3 sample showed a survival rate of 85.31%, indicating that the BC-CTA@PIL membrane of the present invention exceeds the recognized biosafety assessment standard of 80%. The above results emphasize the intrinsic importance of BC materials in optimizing biocompatibility, thereby providing important empirical support for the use of BC-CTA@PIL membranes in fruit packaging.
[0086] Experiment on the application of fresh-keeping of raspberries
[0087] Evaluation method of the applied preservation experiment on raspberries: fresh raspberries with uniform size and color, without physical damage and fungal infection were selected, washed with deionized water, and dried at 25°C. The raspberries were randomly divided into 4 groups. Subsequently, the raspberries were wrapped with commercial PE film, BC film and BC-CTA@PIL film, respectively, and the blank group without film was used as a control. Finally, the raspberries were placed in an artificial climate box at 37°C and RH=70%. All raspberries were stored under ambient conditions (25±2°C) for 9 days, and a digital camera was used to photograph the appearance changes of raspberries during storage.
[0088] In order to evaluate the preservation effect of BC-CTA@PIL composite cling film on raspberries, the composite cling film was used as a packaging material to preserve raspberries. Figure 7 It can be clearly seen in the figure that the raspberries in the blank group shrank and became dull due to water loss on the fifth day, and the fruit decay rate exceeded 20% on the seventh day, which was considered inedible. The raspberries covered with PE packaging were seriously infected with fungi on the third day. The water permeability of PE film was poorer than that of BC-CTA@PIL composite film. The plastic wrap prevented the release of water produced by respiration, trapping the raspberries in a highly humid environment, which promoted the growth of fungi and other microorganisms, resulting in the earliest decayed fruits among all treatments. Compared with the raspberries wrapped in BC-CTA@PIL, the raspberries covered with pure BC showed earlier corruption and partial fungal infection on the seventh day. In sharp contrast, the raspberries stored in the packaging of BC-CTA@PIL showed remarkable elasticity on the ninth day and showed no obvious signs of microbial corruption, thus maintaining the freshness and aesthetic quality of the raspberries. The above results illustrate the effective preservation properties of BC-CTA@PIL, showing its potential as an effective material for extending the shelf life of fresh agricultural products.
Claims
1. An ionic liquid modified bacterial cellulose-based packaging material, characterized in that: The packaging material is obtained by modifying and grafting 1-vinyl-3-aminopropyl imidazole gallic acid ionic liquid on bacterial cellulose.
2. The ionic liquid-modified bacterial cellulose-based packaging material according to claim 1, characterized in that: The packaging material is obtained by reacting bacterial cellulose with N,N'-carbonyldiimidazole and bis(carboxymethyl)trithiocarbonate to obtain modified grafted BC-CTA, and then grafting 1-vinyl-3-aminopropyl imidazole gallic acid ionic liquid on the BC-CTA.
3. A method for preparing an ionic liquid modified bacterial cellulose-based packaging material according to any one of claims 1-2, characterized in that: The following steps are involved: A certain amount of bacterial cellulose is added to dimethyl sulfoxide for full impregnation, and then reacted with N,N'-carbonyldiimidazole (1.4 times the amount of bacterial cellulose) at 30-40°C in the dark, and then the reaction product is reacted with bis(carboxymethyl)trithiocarbonate (1.4 times the amount of bacterial cellulose) at 30-40°C in the dark to obtain BC-CTA; The BC-CTA and 1-vinyl-3-aminopropyl imidazole gallic acid ionic liquid are immersed in dimethyl sulfoxide, and under the action of initiator AIBN, they are sealed and heated to 70-75° C. in an inert gas atmosphere to react, thereby obtaining an ionic liquid-modified bacterial cellulose-based packaging material.
4. The preparation method according to claim 3, characterized in that: The preparation of the 1-vinyl-3-aminopropyl imidazole gallic acid ionic liquid is specifically as follows: First, gallic acid was added to a methanol solution to obtain a 0.2 mmol / mL gallic acid solution, and then an equal amount of 1-vinyl-3-aminopropyl imidazole hydroxide aqueous solution was added to the gallic acid solution, reacted at 0°C for 1 hour, the solvent was evaporated by a rotary evaporator under vacuum, and the product was dried under reduced pressure at 25°C for 24 hours to obtain 1-vinyl-3-aminopropyl imidazole gallic acid ionic liquid.
5. The preparation method according to claim 4, characterized in that: The preparation of the 1-vinyl-3-aminopropyl imidazole hydroxide aqueous solution is specifically as follows: Dissolve 3-bromopropylamine hydrobromide in water, add an equimolar amount of sodium hydroxide, and react to generate 3-bromopropylamine; 1-vinyl imidazole and the 3-bromopropylamine in a molar ratio of 1:1 are refluxed at 60-65° C. under an inert gas atmosphere to obtain 1-vinyl-3-aminopropyl imidazole bromide; The 1-vinyl-3-aminopropyl imidazole bromide is dissolved in water and passed through a 201×7 type anion exchange resin to obtain an aqueous solution of 1-vinyl-3-aminopropyl imidazole hydroxide.
6. The preparation method according to claim 5, characterized in that: The usage amount of the 201×7 type anion exchange resin is 1.3 g of resin per mole of ionic liquid.
7. Use of the bacterial cellulose-based packaging material modified by an ionic liquid according to any one of claims 1-2 in an antibacterial film.
8. The use according to claim 7, characterized in that: Application in food wrap.
Citation Information
Patent Citations
Method for preparing polyvinylidene fluoride blended ultrafiltration membrane with surface-grafted gallic acid
CN107096389A
Polyionic liquid modified bacterial cellulose-based packaging film material as well as preparation method and application thereof
CN118459668A